Induction of Labour in Growth Restricted and Small for Gestational Age Foetuses - A Historical Cohort Study. - Kehl, Sven; Weiss, Christel; Dammer, Ulf; Berlit, Sebastian; Grosse-Steffen, Thomas; Faschingbauer, Florian; Suetterlin, Marc; Beckmann, Matthias; Schneider, Michael (Geburtshilfe und Frauenheilkunde, 2019)
Purpose Induction of labour for small-for-gestational-age (SGA) foetus or intrauterine growth restriction (IUGR) is common, but data are limited. The aim of this study was therefore to compare labour induction for SGA/IUGR with cases of normal foetal growth above the 10th percentile. Material and Methods This historical multicentre cohort study included singleton pregnancies at term. Labour induction for SGA/IUGR (IUGR group) was compared with cases of foetal growth above the 10th percentile (control group). Primary outcome measure was caesarean section rate. Results The caesarean section rate was not different between the 2 groups (27.0 vs. 26.2%, p = 0.9154). In the IUGR group, abnormal CTG was more common (30.8 vs. 21.9%, p = 0.0214), and foetal blood analysis was done more often (2.5 vs. 0.5%, p = 0.0261). There were more postpartum transfers to the NICU in the IUGR group (40.0 vs. 12.8%, p < 0.0001), too. Conclusion Induction of labour for foetal growth restriction was not associated with an increased rate of caesarean section.
EVALuna2:212315